Effect of savirin in the prevention of biofilm-related Staphylococcus aureus prosthetic joint infection - Pant, Narayan; Miranda-Hernandez, Socorro; Rush, Catherine; Warner, Jeffrey; Eisen, Damon P. (Frontiers in Pharmacology, 2022)
Background: Most of the arthroplasty surgery failure due to prosthetic joint infections (PJI) is caused by biofilm-associated Staphylococcus aureus. In a recent experimental study, savirin has been used to prevent and treat S. aureus skin infections in animal models. We explored the application of savirin in a PJI mouse model to determine its utility as an adjunct therapy to prevent PJI. Materials and methods: The effect of savirin treatment on the expression of the key biofilm-related genes (icaA, icaD, eno, fib, ebps, and agr) in S. aureus was studied using qRTPCR. The in-vivo efficacy of savirin alone and with cefazolin to prevent S. aureus PJI was determined using a clinically relevant PJI mouse model. Mice were randomized into five groups (n=8/group): 1)infected K-wire savirin treated group, 2)infected K-wire cefazolin treated group, 3)infected K-wire savirin plus cefazolin treated group, 4)infected K-wire PBS treated group, 5)sterile K-wire group. Savirin was administered subcutaneously immediately post-surgery and intravenous cefazolin was given on day seven. Results: Savirin inhibited planktonic and biofilm in-vitro growth of S. aureus, showed enhanced inhibitory activity when combined with antibiotics, and down-regulated the expression of key S. aureus biofilm-related genes. Savirin significantly reduced bacterial counts in joint implants in comparison with PBS treated control, while savirin plus cefazolin reduced bacterial counts on both implants and peri-prosthetic tissues. Conclusion: Savirin adjuvant therapy may prevent biofilm formation and S. aureus PJI. This study lays a foundation for using savirin for prevention as well as treatment of S. aureus PJI in future animal studies.